A STUDY ON THE ROLE OF RASA-VAHA SROTAS IN PANDU ROGA (AYUSHDHARA, 2018)
This research work is survey study where female patients are randomly selected. The main objective of this research is to observe the Rasavaha Srotas Dusti symptoms as mentioned in Ayurveda as Rasavaha Srotas Vikara and related to Pandu Vikara as one of them using these as subjective criteria’s and to prove this clinically Sahli’s method is used in laboratory as reference. A study was done on 100 female volunteers of different age group to rule out the symptoms of Rasavaha Srotas as explained by the scholars. One cannot see blood getting destructed from naked eyes. It can be seen by signs and symptoms that feel by individual. It happens slowly over many years without our knowledge until pathology occurs. This is an attempt to provide Rasavaha Srotas Dusti Vikara as starting symptoms of Pandu as explained in Ayurveda using modern parameter to access anemia in starting stages.Anemia was seen maximum of 52 % were from the interval of 21-30 age group, and 22 % in age group 31-40 age group, 26 % fall in the age group of 41-50. This shows that incidence of the disease is more among in 21-30 age group.